Remoción de cromo III de aguas de curtido mediante la utilización del exoesqueleto del camarón - Morales Enríquez, María Fernanda (2019)
The preparation of the present titration work demonstrates the study of the removal of chromium found in the tannery waters of the tanning phase, for which experimental tests were carried out based on the adsorption of chromium using the shrimp shell as an adsorbent material. which is similar to cellulose, this material contains 40 percent of chitin that is immersed in the exoskeleton of the crustacean, for the process batch tests were carried out that would contain water prepared with chromium salt at different concentrations and the clean adsorbent material, dry and crushed in different amounts, in order to obtain an adsorption equilibrium point between the adsorbent and the adsorbate in a period of 24 hours. For the measurement of the results, the colorimetric method with the use of EDTA was used to measure the absorbance of chromium in each sample. When obtaining the final concentrations the data were processed, in this way it was estimated that the Langmuir and Freundlich isotherm model was the most optimal since it was adjusted better to the equilibrium of the adsorption and the variables had a significant relationship with the data obtained. Later, we worked with adsorption columns that contained different heights of fixed bed shrimp shell to be able to treat different flows of wastewater from the tanning industry, which had an initial concentration of 24000 mg / l, for this the treatment of the contaminated water, obtaining in this way the corresponding rupture curves, in addition the time of rupture was established for each test, obtaining in the way a removal of chromium III of 90 percent. Finally, the model of Bohart and Adams of continuous system with fixed bed of adsorbent was applied, as a basis to be able to determine the equations for each constantes q0, D0, K1. For the analysis of these results, a linearization of the equations was performed in order to see by means of linear regression the significance that the variables had with the data obtained, which reflected a confidence level of 95 percent.